THE EFFECT OF VIDEO EDUCATION ON BREASTFEEDING SELF EFFICACY IN THRID TRIMESTER PREGANT WOMEN IN THE INDEPENDENT PRATICE OF MIDWIVES IN BENGKULU CITY IN 2023 - Sherina Lumban Toruan; Nur Elly; Rahma Annisa; Mardiani Mardiani; Efrizon Efrizon (Poltekkes Kemenkes Bengkulu, 2023)
Breast milk is the most ideal food source for babies or neonate. Breast milk is easily digested by babies Breast smilk contains a mixture of various food ingredients that are right for babies. Breastfeeding Self-efficacy (BSE) is defined as a mother's confidence in her ability to breastfeed a baby. The purpose of the study was to determine